Fiducijarni prijenos vlasništva i trust : uvodna razmatranja o mogućnosti primjene Haške konvencije o pravu mjerodavnom za trust i o njegovom priznavanju - Karlović, Tomislav, pravnik (Array, 2018)
Considering the main characteristics of fiducia in Roman law, as well as its functions and place within the real property law and the law of obligations, two features that are also prominent in the definition of anglosaxon trust stand out. These are the fiduciary nature of the relationship between the interested parties, as fides (trust) formed the initial basis of both institutes in the period before they were legally recognized, and the transfer of ownership made for specific purpose, different from the regular enjoyment of the object by the owner. However, there is a significant difference between the two (fiducia and trust) becuase of the duality between common law and equity in English legal system. While the mutual interests of the parties to fiducia in Roman law were protected only by personal actions (actiones in personam), parties’ proprietary interests in English trust were (and still are) recognized with the parallel existence of legal and equitable title. In contemporary Croatian law of real property the closest thing to the division of titles exists with regard to the conditionally transferred ownership as regulated in Art. 34 of Ownership and Other Proprietary Rights Act, entaling the division on prior and posterior ownership, both of which can be entered into Land registry and other registries. In the article it is analysed how this division and the following registration of both titles could allow for the effects to be given to trusts, in case it would be pondered on the benefits of accession of Croatia to the Hague Convention on the Law Applicable to Trusts and on their Recognition. Accordingly, after the exposition of Croatian law, it is given a short overview of English trust with emphasis on trusts of land and, subsequently, of the rules of the Hague Convention on the Law Applicable to Trusts and on their Recognition.